Quorum quenching enhanced methane production in anaerobic systems - performance and mechanisms - Liu, Jianbo (2023)
In our previous study, quorum quenching (QQ) bacteria can effectively enhance methane production in an anaerobic membrane bioreactor (AnMBR) while mitigating membrane biofouling. However, the mechanism of such enhancement is unclear. In this study, we analyzed the potential effects from separated hydrolysis, acidogenesis, acetogenesis and methanogenesis steps. The cumulative methane production improved by 26.13%, 22.54%, 48.70% and 44.93% at QQ bacteria dosage of 0.5, 1, 5 and 10 mg strain/g beads, respectively. It was found that the presence of QQ bacteria enhanced acidogenesis step resulting in higher volatile fatty acids (VFA) production, while it had no obvious influence on hydrolysis, acetogenesis and methanogenesis steps. The substrate (glucose) conversion efficiency in acidogenesis step was also accelerated (1.45 folds vs control within first eight hours). The abundance of hydrolytic fermentation gram-positive bacteria and several acidogenic bacteria, such as Hungateiclostridiaceae, was promoted in QQ amended culture, which enhanced VFA production and accumulation. Although the abundance of acetoclastic methanogen Methanosaeta reduced by 54.2% on the 1st day of QQ beads addition, the overall performance of methane production was not affected. This study revealed that QQ had a greater impact on the acidogenesis step in the anaerobic digestion process, though the microbial community in acetogenesis and methanogenesis steps was altered. This work can provide a theoretical basis for using QQ technology to slow down the rate of membrane biofouling in anaerobic membrane bioreactors while increasing methane production and maximizing economic benefits.